The effect of various training variables on developing muscle strength in velocity-based training: A systematic review and meta-analysis - Zhang, X.; Li, H.; Feng, S.; Su, S. (International Journal of Sports Medicine, 2023)
Velocity-based training is an advanced auto-regulation method that uses objective indices to dynamically regulate training loads. However, it is unclear currently how to maximize muscle strength with appropriate velocity-based training settings. To fill this gap, we conducted a series of dose-response and subgroup meta-analyses to check the effects of training variables/parameters, such as intensity, velocity loss, set, inter-set rest intervals, frequency, period, and program, on muscle strength in velocity-based training. A systematic literature search was performed to identify studies via PubMed, Web of Science, Embase, EBSCO, and Cochrane. One repetition maximum was selected as the outcome to indicate muscle strength. Eventually, twenty-seven studies with 693 trained individuals were included in the analysis. We found that the velocity loss of 15 to 30%, the intensity of 70 to 80%1RM, the set of 3 to 5 per session, the inter-set rest interval of 2 to 4 min, and the period of 7 to 12 weeks could be appropriate settings for developing muscle strength. Three periodical programming models in velocity-based training, including linear programming, undulating programming, and constant programming, were effective for developing muscle strength. Besides, changing periodical programming models around every 9 weeks may help to avoid a training plateau in strength adaption.